2017
DOI: 10.1111/cch.12540
|View full text |Cite
|
Sign up to set email alerts
|

Understanding frames: A qualitative study of young people's experiences of using standing frames as part of postural management for cerebral palsy

Abstract: Background: Consensus opinion supports standing frame use as part of postural manage-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Service users and their carers relied heavily on equipment to complete even the most basic aspects of daily life, such as getting out of bed and sitting up. It was interesting that the impact of this essential equipment on participants was found to be both enabling and frustrating, similar to findings from other studies (Goodwin et al., 2018a, 2018b, 2019; Hutton and Coxon, 2011). Notably, participants made little reference to the widely perceived physiological benefits of postural management reported in previous studies (Robertson et al., 2016; Vekerdy, 2007), with only one participant acknowledging a positive impact on breathing.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Service users and their carers relied heavily on equipment to complete even the most basic aspects of daily life, such as getting out of bed and sitting up. It was interesting that the impact of this essential equipment on participants was found to be both enabling and frustrating, similar to findings from other studies (Goodwin et al., 2018a, 2018b, 2019; Hutton and Coxon, 2011). Notably, participants made little reference to the widely perceived physiological benefits of postural management reported in previous studies (Robertson et al., 2016; Vekerdy, 2007), with only one participant acknowledging a positive impact on breathing.…”
Section: Discussionsupporting
confidence: 85%
“…This is the first study to examine both carers’ and service users’ experiences of 24-hour postural management as a whole using focus group methodology. Previous studies have addressed certain elements, such as standing frames, and have focused solely on conditions such as cerebral palsy (Goodwin et al., 2018a, 2018b, 2019), while others have addressed the views of parents, teachers and therapists (Hotham et al., 2017; Hutton and Coxon, 2011; McDonald et al., 2007; Maher et al., 2011; Nicolson et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that three in four adults spent at least 8 h of the 24 h in a day lying (76%) and 8 h or more in sitting (74%). Almost two thirds (67%) of the adults who used standing support used it <1 h per day, which is similar to the 64% previously reported for children in the UK ( 21 ). This finding is concerning, as it implies that adults who use standing devices spend 23 out of the 24 h per day either sitting or lying.…”
Section: Discussionsupporting
confidence: 83%
“…Repetitive exposure to acute pain due to physical therapy, botulinum injections, iatrogenic procedures (e.g. casting, braces, or standing frames) or even daily care (e.g. bathing, dressing, suctioning, etc.…”
Section: What We Know Nowmentioning
confidence: 99%